Does Customs Speed Drive Export Growth? Evidence from the 2024 B-READY Data for Central Asia - Urazova, Nozima (THE INNOVATION ECONOMY, 2026)
Customs clearance efficiency is widely recognized as one of the most actionable dimensions of trade facilitation policy. However, the relationship between procedural speed and actual export growth remains contested in the literature. This paper exploits the 2024 World Bank B-READY data for Central Asia to document and analyze an underappreciated finding: Uzbekistan has the fastest export customs clearance time in the region at 2.3 days, significantly below both the Kazakhstan benchmark (13.0 days) and the Europe and Central Asia regional average (4.5 days). We examine whether this advantage is distributed uniformly across firm types, analyze its institutional underpinnings, and investigate the paradox that fast clearance has not translated into substantially higher export participation. Drawing on the trade facilitation literature and Wilson’s (2003) trade costs framework, we argue that customs speed is a necessary but insufficient condition for export competitiveness, and that complementary factors, including logistics infrastructure, standards compliance, and the availability of export finance, mediate its benefits. We develop and evaluate hypotheses about the conditions under which improvements in border efficiency translate into increases in export volumes, with implications for Uzbekistan’s trade facilitation investment strategy.